2021
DOI: 10.1093/cid/ciab990
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Phase 3 Randomized Clinical Trial of the Safety, Tolerability, and Immunogenicity of 20-Valent Pneumococcal Conjugate Vaccine in Adults Aged ≥18 Years

Abstract: Background Pneumococcal conjugate vaccines (PCVs) have significantly reduced pneumococcal disease, but disease from non-PCV serotypes remains. Safety, tolerability, and immunogenicity of a 20-valent PCV (PCV20) were evaluated. Methods This pivotal phase 3, randomized, double-blind study enrolled adults into 3 age groups (≥60, 50-59, 18-49 years) at US and Swedish sites. Participants were randomized to receive one PCV20 or PCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 32 publications
(42 reference statements)
2
70
1
2
Order By: Relevance
“…Other side effects noted from phase 3 studies include fatigue and headache. Overall, the safety of the PCV20 vaccine is comparable to that of PCV13 in immunocompetent adults 18 years of age and older 58,61–64 . Absolute contraindications to the receipt of the PCV20 vaccine include severe allergic reactions, such as anaphylaxis, to any component of the PCV20 vaccine or to diphtheria toxoid, which is a component of the vaccine 58 .…”
Section: Prevnar 20 (Pcv20)mentioning
confidence: 96%
See 2 more Smart Citations
“…Other side effects noted from phase 3 studies include fatigue and headache. Overall, the safety of the PCV20 vaccine is comparable to that of PCV13 in immunocompetent adults 18 years of age and older 58,61–64 . Absolute contraindications to the receipt of the PCV20 vaccine include severe allergic reactions, such as anaphylaxis, to any component of the PCV20 vaccine or to diphtheria toxoid, which is a component of the vaccine 58 .…”
Section: Prevnar 20 (Pcv20)mentioning
confidence: 96%
“…Absolute contraindications to the receipt of the PCV20 vaccine include severe allergic reactions, such as anaphylaxis, to any component of the PCV20 vaccine or to diphtheria toxoid, which is a component of the vaccine 58 . Unfortunately, safety of the PCV20 vaccine has not yet been assessed in those with immunocompromising conditions, as this patient population was excluded from phase 2 and 3 studies 61–64 . There are also no safety data in patients under the age of 18 or those who are pregnant or breastfeeding.…”
Section: Prevnar 20 (Pcv20)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the some data showed the immunological and clinical safety of PCV15 and PCV20 [36,37], administration of PCV15 followed by PPSV23 was well tolerated and induced comparable antibody levels to PCV13 followed by PPSV23 in healthy adults aged ≥50 years [38]. More significant study results by PCV15 and PCV20 in both basic and clinical fields will be expected especially for the prevention of pneumococcal diseases in these patients.…”
Section: Pneumococcal Vaccine Efficacy/effectiveness and The Next Gen...mentioning
confidence: 97%
“…[30][31][32][33] The vaccination was safe and well tolerated; however, in some studies, a larger proportion of participants who received PCV15 reported injection-site pain when compared with participants who received PCV13. 28,33 ■ Current pneumococcal vaccine recommendations The most recent recommendations for pneumococcal vaccination in adults include two options for those who have never received a PCV: 1) one dose of PCV20 or 2) one dose of PCV15 followed in 1 year by one dose of PPSV23 (see Pneumococcal vaccination recommendations in adults). 19 Pneumococcal vaccination is recommended for all adults age 65 and older as well as for individuals age 19 and older with certain underlying medical conditions (see Indications for early pneumococcal vaccination in adults age ≥19 years).…”
Section: ■ Backgroundmentioning
confidence: 99%